Kinetic Study on the Photo-oxidation of Oxalate Ion by Iodine - Kumar Joshi, Ghanat; Solanki, S.K. (Asian Journal of Chemistry, 2010)
The kinetics of photo-oxidation of oxalate ion in acidic medium by aquo iodine has been investigated at 297 K. The reaction follows identical kinetics and obeys the rate law, rate = k[(COO)2–2][I2][H+]x– where x is less than unity. Addition of Cl– in the form of HCl has no effect on the reaction rate, whereas the reaction product, I– has appreciable influence on the reaction rate. Variation of ionic strength and dielectric constant of the medium and the rate of reaction have been studied.